Comment vous appelez-vous?: Why the French Change Their Names - James E. Jacob; Pierre L. Horn (Names, 1998)
Abstract We examine the history, processes, and motivations which explain in part why and how the French change their names. Studying a small but representative sample of official name changes mandatorily published in the JournaL OfficieL de La République Française at certain moments of post-World War II history (1946, 1963, and 1992-1995), we identify the four most important reasons for changing names: because they are obscene or. pejorative; ridiculous; perceived as too foreign, especially too Arab or too Jewish; or to add the patent of nobility. While we express surprise that names of these kinds still exist in contemporary France, we also recognize that the decision to request a name change at this late date is the last refuge for families who have long suffered indignities and humiliations because of their names.